Adenosine A2A Receptors in the Rat Prelimbic Medial Prefrontal Cortex Control Delay-Based Cost-Benefit Decision Making - Leffa, Douglas T.; Pandolfo, Pablo; Gonçalves, Nélio; Machado, Nuno J.; de Souza, Carolina M.; Real, Joana I.; Silva, António C.; Silva, Henrique B.; Köfalvi, Attila; Cunha, Rodrigo A.; Ferreira, Samira G. (Frontiers in Molecular Neuroscience, 2018)
Adenosine A2A receptors (A2ARs) were recently described to control synaptic plasticity and network activity in the prefrontal cortex (PFC). We now probed the role of these PFC A2AR by evaluating the behavioral performance (locomotor activity, anxiety-related behavior, cost-benefit decision making and working memory) of rats upon downregulation of A2AR selectively in the prelimbic medial PFC (PLmPFC) via viral small hairpin RNA targeting the A2AR (shA2AR). The most evident alteration observed in shA2AR-treated rats, when compared to sh-control (shCTRL)-treated rats, was a decrease in the choice of the large reward upon an imposed delay of 15 s assessed in a T-maze-based cost-benefit decision-making paradigm, suggestive of impulsive decision making. Spontaneous locomotion in the open field was not altered, suggesting no changes in exploratory behavior. Furthermore, rats treated with shA2AR in the PLmPFC also displayed a tendency for higher anxiety levels in the elevated plus maze (less entries in the open arms), but not in the open field test (time spent in the center was not affected). Finally, working memory performance was not significantly altered, as revealed by the spontaneous alternation in the Y-maze test and the latency to reach the platform in the repeated trial Morris water maze. These findings constitute the first direct demonstration of a role of PFC A2AR in the control of behavior in physiological conditions, showing their major contribution for the control of delay-based cost-benefit decisions.